Applied chemistry demonstration learning for the Indonesian students' association in Taiwan - Anugrah Ricky Wijaya; Alif Alfarisyi Syah; Irma Kartika Kusumaningrum; Dima Vici Nadia Ariefianti; Angga Dheta Shirajjudin Aji; Khoiril Amin (Department of Chemistry, Universitas Negeri Malang, 2025)
Indonesian migrant workers (TKI) in Taiwan face various challenges, including social inequality, limited access to educational resources, and a general lack of community support. To address these issues, the Chemistry Department of UM provided training to PPI Chung Yuan Christian University (CYCU) Taiwan, equipping them to run programs featuring demonstrations of micro-scale chemical applications, including cation and anion determination, electrolysis, and the production of soap and candles. These hands-on activities aim to develop scientific skills among the younger generation and empower migrant workers with entrepreneurial knowledge for their lives in Taiwan. Program outcomes were evaluated through surveys assessing participants' understanding and satisfaction with micro-scale demonstrations and the production of soap and candles. Results indicated that electrolysis and aromatherapy soap-making were particularly well-received, as they were easier to understand and gained popularity, with participants passing on the skills to other migrant workers. Efforts were made to ensure the program’s sustainability by actively involving the TKI community, with the hope that this initiative will help migrant workers develop valuable skills, broadening their opportunities for future success.References Angelica, R., Yoana Ledy Mutiara, Mufid Muhammad, & Salsabila Nink. (2023). Peranan Hukum Internasional Dalam Upaya Melindungi Tenaga Kerja Indonesia (TKI) di Taiwan. Das Sollen: Jurnal Kajian Kontemporer Hukum Dan Masyarakat, 1(02 SE-Articles). https://journal.forikami.com/index.php/dassollen/article/view/300 Cahyadi, N., & Baskoro, H. (2022). Sosialisasi kewirausahaan pada pekerja migran indonesia dengan design thinking. DedikasiMU : Journal of Community Service, 4(3), 282–289. https://journal.umg.ac.id/index.php/dedikasimu/article/view/4164 Damarsidi, H. R. (2017). Analisis Anomali Kebijakan Penempatan TKI: Eksploitasi Tenaga Kerja Indonesia sebagai Anak Buah Kapal Perikanan Taiwan. Journal of International Relations, 3(4), 40–48. Kartikasari, D., & Muthmainah, M. (2023). Pengaruh Pelatihan Keterampilan Koping Orang Tua terhadap Kecerdasan Emosi & Keterampilan Sosial Anak. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 7(5 SE-Articles), 5506–5522. https://doi.org/10.31004/obsesi.v7i5.5100 Kwartawaty, N. N., Noviana, E., & Mahardhika, G. T. (2020). Pelatihan mini MBA secara daring terhadap pekerja migran Indonesia di Taiwan. BERNAS: Jurnal Pengabdian Kepada Masyarakat, 1(4 SE-Articles), 661–666. https://doi.org/10.31949/jb.v1i4.543 Raharto, A. (2017). Pengambilan Keputusan Tenaga Kerja Indonesia (TKI) Perempuan Untuk Bekerja di Luar Negeri: Kasus Kabupaten Cilacap. Jurnal Kependudukan Indonesia, 12(1), 39–54. Rahman, R. A., Salim, A. A., & Anggriawan, R. (2021). Peran Pemerintah Indonesia dan Taiwan dalam Menanggulangi Kasus Pekerja Migran Indonesia “Kaburan.” Jurnal Wawasan Yuridika, 5(1), 81–99. https://ejournal.sthb.ac.id/index.php/jwy/article/view/414 Ramadhan, M. Z., & Amaliyah, R. (2023). Strategi indonesia dalam manajemen perlindungan pekerja migran Indonesia di Taiwan pasca new southbound policy. SIYAR Journal, 3(1 SE-Articles), 74–90. https://doi.org/10.15642/siyar.2023.3.1.74-90